2018
DOI: 10.1155/2018/1392975
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Metaplasia of the Cervix: A Rare Transformation Can Mimic a Tumor—Literature Review

Abstract: Background The transformation of nonosseous soft tissue into bone is known as osseous metaplasia (OM). This condition most commonly affects the musculoskeletal and central nervous systems and it is a well-known phenomenon in different soft tissue organs. Rarely, OM can affect the uterus, which can extend into the cervix. OM affecting the cervix alone is a more rare condition that has multiple different clinical presentations. The presentation can be similar to that of a tumor in extremely rare cases. Case Summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies have shown that non-osteogenic mesenchymal cells, such as extramedullary fat and myoblasts, may undergo osteogenic differentiation in the presence of BMP-2 (Jacono et al, 2001). Others have postulated that repeated trauma could induce osseous metaplasia, which could be pertinent to our patient who endured recurrent rectal prolapse on defecation (Alsaqobi and Al-Brahim, 2018).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Studies have shown that non-osteogenic mesenchymal cells, such as extramedullary fat and myoblasts, may undergo osteogenic differentiation in the presence of BMP-2 (Jacono et al, 2001). Others have postulated that repeated trauma could induce osseous metaplasia, which could be pertinent to our patient who endured recurrent rectal prolapse on defecation (Alsaqobi and Al-Brahim, 2018).…”
Section: Discussionmentioning
confidence: 73%
“…Osseous metaplasia in mucosal polyps, although rare, is a phenomenon that has been reported in the various organs such as nasopharynx, endocervix among others (Jacono et al, 2001; Alsaqobi and Al-Brahim, 2018). Osseous metaplasia in benign colorectal polyps is very rare, with only 21 previous cases (Amir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Second, another example of the plasticity of the smooth muscle cells is that osseous metaplasia is reported in normal endometrium and cervix even without any history or presence of neoplasms [22,23]. The cell fate of smooth muscle is not strictly confi ned to contractile phenotype, suggesting the potential of smooth muscle to transform other cell types such as osteoblasts which secrete osteoid and form osseous metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Osseous metaplasia has been described in many tissues, most commonly in musculoskeletal and central nervous system, followed by soft tissue organs [1,2]. In the female genital tract osseous metaplasia is reported as a rare condition in cervix and vagina, and it is more often found in endometrium [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Osseous metaplasia has been described in many tissues, most commonly in musculoskeletal and central nervous system, followed by soft tissue organs [1,2]. In the female genital tract osseous metaplasia is reported as a rare condition in cervix and vagina, and it is more often found in endometrium [2][3][4]. In ovary it is a rare entity and is usually associated with cystic teratoma, mucinous cystadenoma [5], papillary serous cystadenocarcinoma [6], endometrioid adenocarcinoma [7] and thecoma [8].…”
Section: Introductionmentioning
confidence: 99%